Deep Inferior Epigastric Perforator Versus Free Transverse Rectus Abdominis Myocutaneous Flap: Complications and Resource Utilization. Issue 5 (May 2017) - Zoghbi, Yasmina; Gerth, David J.; Tashiro, Jun; Golpanian, Samuel; Thaller, Seth R.
Abstract : Introduction: Abdominal based breast reconstruction exists in a continuum from pedicled transverse rectus abdominis myocutaneous (TRAM) flap to deep inferior epigastric perforator (DIEP) free flap. DIEP flap has the advantage of complete rectus abdominis sparing during harvest, thus decreasing donor site morbidity. Aim of this study is to determine whether the surgical advantages of the DIEP flap impact postoperative outcomes versus the free TRAM flap (fTRAM). Methods: We reviewed the Nationwide Inpatient Sample database (2010–2011) for all cases of DIEP and fTRAM breast reconstruction. Inclusion criteria were: female sex and patients undergoing DIEP or fTRAM total breast reconstruction. Male sex was excluded from the analysis. We examined demographic characteristics, hospital setting, insurance information, patient income, comorbidities, postoperative complications (including reoperation, hemorrhage, hematoma, seroma, myocardial infarction, pulmonary embolus, wound infection, and flap loss), length of stay, and total charges (TCs). Bivariate and multivariate analyses were performed to identify independent risk factors of increased length of stay and TCs. Results: Fifteen thousand eight hundred thirty-six cases were identified. Seventy percent were white, 97% were insured, and 83% of patients were treated in an academic teaching hospital setting. No mortalities were recorded. The DIEP cohort was more likely to be obese ( P = 0.001). Free TRAM cohort was more likely to suffer pneumonia ( P < 0.001; odds ratio [OR], 3.7), wound infection ( P = 0.001; OR, 1.7), and wound dehiscence ( P < 0.001; OR, 4.3). Type of reconstruction did not appear to affect risk of revision, hemorrhage, hematoma, seroma, or flap loss. Total charges were higher in the DIEP group ( P < 0.001). Multivariate analysis demonstrated that fTRAM was an independent risk factor for increased length of stay ( P < 0.001; OR, 1.6), and DIEP was an independent risk factor for increased TCs ( P < 0.01; OR, 1.5). There was no significant difference in postoperative complications. Conclusions: The fTRAM cohort was more likely to develop surgical site complications and have an increased length of stay, but TCs were higher for the DIEP group.